The Effect of Exchange Rate and Inflation on the Composite Stock Price Index - Taufik Sadikin R; Mohamad Lutfi (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2022)
The Composite Stock Price Index is the main board index that reflects the stock index listed on the capital market. Macroeconomics is the benchmark to determine the movement of the Composite Stock Price Index in the capital market, one of which in this study is the exchange rate and inflation. The purpose of this study is to find out how much influence the exchange rate variable has on the Composite Stock Price Index, to find out how much influence the inflation variable has on the Composite Stock Price Index, and to find out how much influence the exchange rate and inflation variables have on the Composite Stock Price Index. The research method used in this study is descriptive and verification method and the type of sample used is random sampling where all populations are entitled to be part of the sample with the analytical method used is multiple linear regression. The results of this study indicate that the exchange rate has a negative effect on the Composite Stock Price Index and inflation partially has no effect on the Composite Stock Price Index, while simultaneously in this study, the Composite Stock Price Index responds to the influence of the exchange rate and inflation.